2017
DOI: 10.1142/s0218216517500936
|View full text |Cite
|
Sign up to set email alerts
|

Knot fertility and lineage

Abstract: In this paper, we introduce a new type of relation between knots called the descendant relation. One knot H is a descendant of another knot K if H can be obtained from a minimal crossing diagram of K by some number of crossing changes. We explore properties of the descendant relation and study how certain knots are related, paying particular attention to those knots, called fertile knots, that have a large number of descendants. Furthermore, we provide computational data related to various notions of knot fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…Related work. Besides proving the result mentioned above on the shadows in Figure 1, Cantarella, Henrich, Magness, O'Keefe, Perez, Rawdon, and Zimmer investigate in [1] several problems related to Question 1.1, including an exhaustive analysis on shadows of minimal crossing diagrams of knots with crossing number at most 10.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Related work. Besides proving the result mentioned above on the shadows in Figure 1, Cantarella, Henrich, Magness, O'Keefe, Perez, Rawdon, and Zimmer investigate in [1] several problems related to Question 1.1, including an exhaustive analysis on shadows of minimal crossing diagrams of knots with crossing number at most 10.…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, we only consider two particular types of tangles, illustrated in Figure 6. A tangle is of Type I if it consists of a string λ with endpoints (−1, −1, 0) and (−1, 1, 3), and a string ρ with endpoints (1, −1, 0) and (1,1,3), and it is of Type II if it consists of a string λ with endpoints (−1, −1, 0) and (−1, 1, 3), and a string ρ with endpoints (1, 1, 0) and (1, −1, 3).…”
Section: A Kind Of Shadow Inspired Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this effect is doubtless due to the presence of composite knot types in our data such as +3 1 #+3 1 . However, we suspect that other knots in the same family, such as +5 1 , also contain subarcs classified as the trefoil knot [7,9,17,23,30,33,35].…”
Section: Experiments Measuring Positive Predictive Valuementioning
confidence: 98%
“…Originally envisioned as a way to distinguish different atomic properties [48], modern work has suggested that a classification system could assist in the understanding of glueball particles [20]. Since then a series of systems have been suggested for ordering or relating knots within these ever expanding tabulations [10,13].…”
Section: Introductionmentioning
confidence: 99%